Nanofertilizers for agricultural and environmental sustainability. (April 2022) - Babu, Subhash; Singh, Raghavendra; Yadav, Devideen; Rathore, Sanjay Singh; Raj, Rishi; Avasthe, Ravikant; Yadav, S.K.; Das, Anup; Yadav, Vivek; Yadav, Brijesh; Shekhawat, Kapila; Upadhyay, P.K.; et al.
Abstract: Indiscriminate use of chemical fertilizers in the agricultural production systems to keep pace with the food and nutritional demand of the galloping population had an adverse impact on ecosystem services and environmental quality. Hence, an alternative mechanism is to be developed to enhance farm production and environmental sustainability. A nanohybrid construct like nanofertilizers (NFs) is an excellent alternative to overcome the negative impact of traditional chemical fertilizers. The NFs provide smart nutrient delivery to the plants and proves their efficacy in terms of crop productivity and environmental sustainability over bulky chemical fertilizers. Plants can absorb NFs by foliage or roots depending upon the application methods and properties of the particles. NFs enhance the biotic and abiotic stresses tolerance in plants. It reduces the production cost and mitigates the environmental footprint. Multitude benefits of the NFs open new vistas towards sustainable agriculture and climate change mitigation. Although supra-optimal doses of NFs have a detrimental effect on crop growth, soil health, and environmental outcomes. The extensive release of NFs into the environment and food chain may pose a risk to human health, hence, need careful assessment. Thus, a thorough review on the role of different NFs and their impact on crop growth, productivity, soil, and environmental quality is required, which would be helpful for the research of sustainable agriculture. Graphical abstract: Image 1 Highlights: Nanofertilizers (NFs) are the best alternative to traditional chemical fertilizers. Nutrients use efficiency of NFs is higher than the conventional chemical fertilizers. NFs can increase the tolerance of plants against biotic and abiotic stresses. Supra optimal dose of NFs had a negative impact on crops, soil, and the environment.